Concerns of parents regarding their children’s transition from the Nursery School to the compulsory education of the Kindergarten - Σακελλαρίου Μαρία; Αναγνωστοπούλου Ροδόκλεια (Education Sciences, 2023)
The nursery school plays an important role in preparing children for their entry into compulsory education and skills acquisition. The aim of our study was to detect parental concerns as to their children’s transition from Nursery School to Kindergarten coupled with their expectations regarding preschool environment. As a basic instrument to record parental views on transition issues, semi-structured interview was opted so that valid data and thorough information be gathered concerning our study. Our research sample consisted of 55 families all from the Region of Epirus. Based on the findings of our research, the primary concern that occurred, with regards to the child’s transition to the kindergarten, was -on the parents’ side- the acclimation on the new context and the socialization. In addition, it was found that parents have high expectations of the kindergarten as they expect their children to prepare for the first grade of primary school through the promotion of basic learning concepts. According to the research, the awareness and active participation of families in the transition process can ensure a healthy start in compulsory education for the child.